Visualizing the near-field coupling and interference of bonding and anti-bonding modes in infrared dimer nanoantennas - Alonso Gonzalez, Pablo (2013)
We directly visualize and identify the capacitive coupling of infrared dimer antennas in the near field by employing scattering-type scanning near-field optical microscopy (s-SNOM). The coupling is identified by (i) resolving the strongly enhanced nano-localized near fields in the antenna gap and by (ii) tracing the red shift of the dimer resonance when compared to the resonance of the single antenna constituents. Furthermore, by modifying the illumination geometry we break the symmetry, providing a means to excite both the bonding and the ?dark? anti-bonding modes. By spectrally matching both modes, their interference yields an enhancement or suppression of the near fields at specific locations, which could be useful in nanoscale coherent control applications.